Effect of Hydroxyurea Therapy on Renal and Liver Function Tests and Modulation of Red Cell Concentrate Requirement in Transfusion Dependent Beta-Thalassemia Patients - Zahoor, Saiqa (International Journal of Pathology, 2023)
Background: Raised fetal hemoglobin (HbF) levels in patients with Transfusion Dependent Beta Thalassemia (TDBT) are now known to contribute to increase in the total hemoglobin level, reduce ineffective erythropoiesis and reduce hemolysis due to prolonged survival of RBCs. Experience with hydroxyurea as an HbF inducer in Sickle Cell Disease (SCD) patients prompted researchers to conduct trials regarding this therapy in other hemoglobinopathies.Material and Methods: It was a retrospective study. Non probability consecutive sampling technique was applied. A total of 265 splenectomized patients older than 2 years of age who had been treated with hydroxyurea for at least 12 months were selected. The patients were registered at the Hematology Day Care Center of the Hayatabad Medical Complex (HMC), Peshawar from January 2014 to January 2018.Results: The number of transfused Red Cell Concentrate (RCC) units, reduced from 27.46 to 22.37 during the 12 months pre and 24 months post treatment period. The total hemoglobin (Hb) levels of 8.4 g/dL at 12 months pre-treatment increased to 8.9 g/dL at 12 months post-treatment, but without any statistical significance. Mean inter-transfusion time improved from 3.2 weeks to 7.4 weeks. No statistically significant difference was found in renal function tests in pre and post treatment groups. Although Alanine aminotrasferase (ALT) and Aspartate aminotransferase (AST) showed statistically significant differences in pre and post-treatment groups, yet these differences were not clinically significant.Conclusion: Hydroxyurea therapy significantly decreased the RCC packs required to maintain adequate hemoglobin levels while increasing the time period between successive transfusions of RCC in patients with TDBT without any significant renal and hepatic adverse effects.